Effect of three energy levels on body weight change, nutrient utilization,rumen biochemical profiles and semen quality in rams - RAO, S B N; DINESHKUMAR, D; RAJU, PRIYADARSHINI; CHANDRASEKHARAIAH, M; THULASI, A; JOSE, V LYJU; SELVARAJU, S (The Indian Journal of Animal Sciences, 2012)
In the present experiment, 21 rams of uniform body weight and age ( 1 year) were equally divided into 3 groups to find out the effect of 3 levels of energy, viz. control, low and high energy on growth, nutrient utilization, rumen biochemical profiles and semen quality. Body weight gain increased significantly compared to control and low energy. FCR improved significantly in high energy supplemented groups. Intake of DDM, DOM and TDN were significantly higher in high energy and control groups as compared to low energy group, with similar intake of CP and DCP in all groups. N-balance (g/d) was significantly higher in high energy group as compared to low energy group. Fractionation of VFA revealed a shift in propionate with narrower acetate to propionate ratio in high energy group favoring more body weight gain. Significantly higher semen volume (ml), mass activity (0–5 score) and progressive forward motility (%) were observed in optimum energy group compared to low energy group with no added benefit in high energy supplemented group. It is concluded that energy rich diets tend to increase weight gain of young rams with a shift in rumen volatile fatty acid concentration to propionate side. Nutritional strategies for feeding rams primarily reared for semen production have to be formulated critically as supplemented energy is being diverted for body weight gain rather than improving semen quality.